On Almost $τ^\star(σ_1,σ_2)$-continuity and Weak $τ^\star(σ_1,σ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of almost $τ^\star(σ_1,σ_2)$-continuous functions and weakly $τ^\star(σ_1,σ_2)$-continuous functions. Moreover, some characterizationsof almost $τ^\star(σ_1,σ_2)$-continuous functions and weakly $τ^\star(σ_1,σ_2)$-continuous functions are investigated. Furthermore, the relationships between almost $τ^\star(σ_1,σ_2)$-continuity and weakly $τ^\star(σ_1,σ_2)$-continuity are considered.